PENGARUH PENDIDIKAN TERHADAP MOBILITAS SOSIAL - Arif Zamhari (STAI Ma'had Aly Al-Hikam Malang, 2012)
Every state which wish to move forward and improve its people prosperity, hence cymbal of a national development. There no development theory going into effect universal for all nation, each determining its own national development model, there no original pattern of modernization which must be imitated by nations not yet gone forward, and each nation own possibilities modernize by self. Natonal development intrinsically aims to look for addad value of and addad values in order to the tomorrow day of life better than today, covering spiritual and corporeal prosperity, and earthly of ukhrowi. National development always experience of ever greater challenge, complex and insist on as effect of science progress and esident accretion and technological and also interaction with other nations in international life configuration. All this cause the happening of value friction, good of base value which is concerning belief and religion, and also the instrument which is concerning science and technological.